Consumer's openness to cashless payment methods in hotels and the factors influencing it - Agalla, Timothy C.; Mondejar, Rey G.; Villanueva, Kyla C. (2022.)
Even before the COVID-19 pandemic, businesses were already exploring, and even employing, the use of cashless methods in customer payment transactions as a value-adding feature that improves overall customer experience. This research study was conducted to provide a descriptive and quantitative assessment on the existing consumers' openness in Iloilo City to the digital payment methods in hotels and to identify the factors influencing it. The researchers used a descriptive single cross-sectional research design to describe consumers' awareness, motivation and attitude, their associated risk tolerance, and their overall openness to these options. With graphed frequency distribution and ran T-test and One-way Anova test to determine consumers' preferences and compare means to examine current significant differences between consumers' openness to cashless payment options and the demographics, the study disproves that variables sex, age, income, motivations, and civil status are determining factors for overall openness to cashless payment methods. Furthermore, results show that 97% of the respondents are aware of these cashless payment options and 74% of the respondents have made a cashless transaction, regardless of how frequent. The researchers recommend hotel businesses to invest in necessary creations and acquisitions, to respond and ease fraud and cybersecurity concerns, notice on information storage and use, and association with reliable third-party systems, to conduct a separate and independent quick survey on the preferred e-wallet platforms and bank accounts so they can determine which ones are widely used and more profitable, and, most importantly, study merchant adoption.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, June 2022.